HYPERLIPIDAEMIA PATIENTS ATTENDING THE IIUM FAMILY HEALTH CLINIC, KUANTAN: A SURVEY ON THEIR MEDICATION ADHERENCE AND KNOWLEDGE ON HYPERLIPIDAEMIA - MD AKHIR, NUR HANI; ABDUL HADI, AZWANIS; ZAINUDDIN , NORAFIZA (International Journal of Allied Health Sciences, 2020)
Introduction: Hyperlipidaemia is one of the major diseases that could lead to cardiovascular related death and affects nearly half of the Malaysian population. Adherence to hyperlipidaemia medications is important to ensure good control of the disease. Objectives: This study aims to evaluate the level of patients’ adherence to hyperlipidaemia medication, to identify the level of knowledge on hyperlipidaemia and its treatment medication and lastly to determine the significant associated factors for poor adherence among hyperlipidaemia patients in the International Islamic University Malaysia (IIUM) Family Health Clinic (FHC). Methodology: This cross sectional study was conducted through distribution of self-administered questionnaire in IIUM FHC to assess the level of medication adherence and knowledge. The total cumulative score derived from the knowledge section was categorised into high and low knowledge based on the median score. The significant associated factors of adherence level were analysed using chi-square test. Results: The results showed that only 41.3% of patients adhered to medication and 62.4% demonstrated a high level of knowledge. Factors of gender, age, educational level, employment status, income, religion, race, marital and living status, duration of illness and level of knowledge were not significantly associated with adherence level (p> 0.05). Conclusion: There is low level of adherence rate, there is high level of knowledge regarding hyperlipidaemia and its treatment. Lastly, there is no significant association between all variables or factors present because of limitation in sample size and other items of measurement. The main reason for non adherence to medication is forgetfulness followed by other six factors. Implication: This study is important to help the clinicians to understand more about their patients and initiate an action in order to improve the treatment adherence. This study might initiate the patients and community to be more aware of this disease.